Response to salt stress and strategies to improve salt tolerance in Chinese kale (Brassica oleracea var. alboglabra) - Tayebi-Meigooni, Amin (2012)
Despite the large body of literature on salinity stress, our knowledge about the effects of salt stress on Chinese kale (Brassica oleracea var. alboglabra) is still little. Therefore, there is a pressing need to know in more detail how an important vegetable plant as Chinese kale responds and adapts to such conditions. With regard to the importance of Chinese kale in term of their benefits and high consumption in human diets, understanding the possible effects of salt stress on Chinese kale have never been exposed to salt stress can be significant. Therefore attempts to provide some practical, safe and environmentally sound techniques to retain productivity under salt stress is critical. The purposes of this study were to unveil the mechanism contributing to salinity tolerance during vegetative stage and to test for possible contribution of exogenous ascorbic acid and pre-treatment with low concentration of hydrogen peroxide in association with the tolerance mechanisms during vegetative development of the crop. Preliminary study involving four cultivars of Chinese kale [‘Standard kailan’,‘Hong Kong kailan’, ‘Kale Curly Leaf’ and ‘Hong Kong Stem Flower’] and four salinity levels (0, 25, 50 and 75) showed that final growth parameters, relative water content, concentration of photosynthetic pigments and maximum quantum yield of PSII (Fv/Fm) were significantly reduced by salinity. The treatment elevated plant's proline, hydrogen peroxide and lipid peroxidation. Among cultivars tested, cv. ‘Standard kailan‘ showed minimum reduction of biomass. Cv. ’Standard kailan‘ also showed relatively higher adaptability to salinity due to its ability to regulate hydrogen peroxide (H2O2) generation and moderate oxidative damage to cell membranes as shown by malondialdehyde (MDA) content in leaf tissues at all salinity. Based on the results, cv. ‘Standard kailan‘ was more salt-tolerant than other cultivated varieties and has been used for further experimentation. Biochemical analysis of the leaves revealed that salinity also produced significant negative impacts on protein synthesis and leaf pigments (chlorophylls and carotenoid). The results may imply the increase in the energy dissipation via chlorophyll fluorescence along with reduction of chlorophylls maybe is a manifestation to preserve a balance between harvesting and utilizing energy in order to reduce threat of oxidative stress. Consistent with results in the first experiment, detrimental effects of salinity were further illustrated in the generation and accumulation of hydrogen peroxide and MDA. However, salt stressed plants contained relatively higher concentrations of proline and activity of antioxidant enzymes especially ascorbate peroxidase (APX) and peroxidase (POX). Chinese kale was shown to be not affected by low salinity up to 25 mM and can be tolerant up to 75 mM NaCl. Subsequent study further confirmed the results of the first experiment where the overall reduction in plant growth was coupled with reduced leaf expansion and net assimilation rate. Negative effects of salinity are clearly shown as reduction in net assimilation rate (NAR) and relative growth rate (RGR) and this was coupled with alteration of ionic balance in the plant tissue. Salinity reduced N, K+, Ca2+ and Mg2+ in leaves and roots. P was also decreased by the treatment in leaves, while it was increased in root. The concentrations of Na+ and Cl- in leaves were markedly enhanced in plants tissues as the NaCl in the root zone increases. Reduction of N and Mg2+ availability for various processes such as chlorophyll biosynthesis, lack of P of bioenergetics pathway, besides imbalance of K+ and Ca2+ and negative effects of Na+ and Cl- to different bioactive processes were also considered to be responsible for growth reduction in this plant.